CRISPR/Cas9: implication for modeling and therapy of amyotrophic lateral sclerosis - Shi, Yajun; Zhao, Yan; Lu, Likui; Gao, Qinqin; Yu, Dongyi; Sun, Miao (Frontiers in Neuroscience, 2023)
Amyotrophic lateral sclerosis (ALS) is a deadly neurological disease with a complicated and variable pathophysiology yet to be fully understood. There is currently no effective treatment available to either slow or terminate it. However, recent advances in ALS genomics have linked genes to phenotypes, encouraging the creation of novel therapeutic approaches and giving researchers more tools to create efficient animal models. Genetically engineered rodent models replicating ALS disease pathology have a high predictive value for translational research. This review addresses the history of the evolution of gene editing tools, the most recent ALS disease models, and the application of CRISPR/Cas9 against ALS disease.